Interplay of KIR2DL5, nitric oxide, and tobacco smoking in predisposition to bladder cancer - Ruiz-Lorente, Inmaculada; Gimeno, Lourdes; López-Abad, Alicia; López Cubillana, Pedro; Fernández Aparicio, Tomás; Jesús Asensio Egea, Lucas; Moreno Avilés, Juan; Doñate Iñiguez, Gloria; Guzmán Martínez-Valls, Pablo Luis; Server, Gerardo; Ferri, Belén; Campillo, José Antonio; et al. (Frontiers in Cell and Developmental Biology, 2025)
IntroductionTobacco smoking is the most significant risk factor for bladder cancer (BC), followed by other environmental and dietary exposures. However, major genetic determinants remain unidentified. The objective of this work was to investigate the potential association of killer-cell immunoglobulin-like receptor 2DL5 (KIR2DL5) with BC risk, its interaction with tobacco smoking, and the underlying immune mechanisms.MethodsThis case-control study analyzed KIR genotype in patients with BC (n = 325), as well as in healthy controls (HC, n = 925) and patients with other cancers (n = 862) as control groups. Immune assays assessed proliferation, cytotoxicity, cytokine, and intracellular nitric oxide (icNO) production by NK and T cells after anti-CD3/CD28 or Bacillus Calmette-Guérin (BCG) stimulation in 24 donors stratified by KIR2DL5 genotype. Multivariate logistic regression was used to evaluate BC predisposition.ResultsThe frequency of KIR2DL5 was higher in BC patients than in HC (64.6% vs. 53.6%, p = 0.004). Linear regression analysis revealed that, independent of other aKIRs within the B haplotype, KIR2DL5 was associated with BC susceptibility (HR = −1.167, p = 0.050), alongside other significant factors such as sex (HR = −1.465, p < 0.001), age (HR = −0.181, p < 0.001), and tobacco smoking (HR = −2.454, p < 0.001). The frequency of KIR2DL5 was higher among non-smokers compared to smokers in both healthy controls (61.4% vs. 44.6%, p < 0.05) and BC patients (72.9% vs. 60.8%, p < 0.05). Among non-smoking BC patients, KIR2DL5 was more frequently observed in small-sized (<3 cm), solid-pattern, non-muscle-invasive BC cases. Immune profiling revealed that KIR2DL5 was associated with increased icNO production by NK and T cells but showed no association with proliferation, cytokine secretion, or cytotoxicity.DiscussionKIR2DL5 is independently associated with BC, regardless of age, sex, or tobacco smoking status. While the immunological mechanisms remain unclear, enhanced nitric oxide production by immune effector cells may play a role in this association.